L’offre active une culture de respect, une culture d’excellence : guide complet [infographie] - Commissariat aux langues officielles (2017)

An evaluation of FrancoForme: A case-managed home-based primary and secondary cardiovascular disease prevention program for French-speaking Canadians - Prince, Stephanie. A.; Laflamme, Marc; Harris, Jennifer; Tulloch, Heather E.; de Margerie, Michele (Journal of cardiopulmonary rehabilitation and prevention, 2017)
Purpose: Cardiovascular disease (CVD) is the leading cause of mortality globally. Telephone-delivered interventions targeting cardiovascular risk factors are gaining popularity. This study is an evaluation of FrancoForme, a cardiovascular risk factor reduction program for the primary and secondary prevention of CVD among French-speaking patients of Eastern Ontario. Methods: This study reports on changes in cardiovascular risk factors, weekly exercise levels, and psychosocial characteristics including anxiety, depression, and quality of life upon program completion (3 months) and at 1 year after the start of the program. Repeated-measures analysis of variance was used to compare changes in outcomes between primary prevention risk groups (low, moderate, and high risk for CVD) and the secondary prevention group (ie, cardiac rehabilitation) at baseline, 3 months and 12 months. Results: A total of 762 patients enrolled in FrancoForme between 2008 and 2015. At 3 months, all program completers (n = 507) experienced significant reductions for all cardiovascular risk factors except diastolic blood pressure. Minutes of self-reported exercise increased significantly by an average 90 minutes per week and all psychosocial variables improved. Significant group effects were observed across several risk factors. Among 12-month responders (n = 240), exercise, high-density lipoproteins, triglycerides, cholesterol, and all psychosocial variables were improved over baseline results. Conclusions: FrancoForme is unique in targeting both the primary and secondary prevention of CVD and removes several of the barriers to participating in a conventional CVD prevention program for French-speaking patients. FrancoForme is successful, receiving high satisfaction rates and resulting in significant improvements in cardiovascular risk factors, exercise, anxiety, and depression, as well as quality of life.

Behaviours demonstrating active offer: Identification, measurement, and determinants - Savard, Jacinthe; Casimiro, Lynn; Bouchard, Pier; Benoît, Josée (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Les comportements favorables à l’offre active, leur mesure et leurs déterminants - Savard, Jacinthe; Casimiro, Lynn; Bouchard, Pier; Benoît, Josée (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Dans ce chapitre, nous présenterons comment nous avons répertorié des comportements favorables à une offre active (OA) de services sociaux et de santé en français en contexte minoritaire, comment nous les avons mesurés et comment nous avons utilisé ces mesures pour déceler des déterminants de l’OA. Nous présentons en détail l’élaboration des outils qui ont servi à mesurer les comportements d’OA, le soutien organisationnel perçu envers l’OA et les caractéristiques personnelles qui peuvent influer sur les comportements d’OA (déterminants). Diverses méthodes quantitatives ont été utilisées pour atteindre ces objectifs. Les résultats obtenus démontrent la présence d’un fort lien entre le soutien organisationnel perçu et les comportements individuels d’OA. À soutien organisationnel égal, les caractéristiques individuelles associées à une plus grande propension à démontrer des comportements d’OA incluent une formation sur l’OA, l’affirmation identitaire et la compétence en français. Le sentiment de compétence en anglais est quant à lui associé négativement aux comportements individuels d’OA de services en français. Une meilleure connaissance de ces déterminants permet de raffiner les stratégies de sensibilisation et d’éducation des futurs professionnels de la santé et des services sociaux envers l’OA. Mots-clés : comportements d’offre active, mesure, déterminants, soutien organisationnel, comportements individuels, recherche quantitative.